2006
DOI: 10.1093/ps/85.3.462
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wheat quality on digestion differ between the D+ and D- chicken lines selected for divergent digestion capacity

Abstract: The aim of the experiment was to study the effects of 2 wheat cultivars (Baltimor and Scipion) with different hardness values (75 and 5, respectively) on 2 divergent lines (D+ and D-) of broiler chickens selected on the basis of their digestion ability assessed by AME(n). Wheat was incorporated at 54.6% in diets. The other main ingredients were soybean meal (35.3%) and rapeseed oil (5.5%). Diets were given as pellets from 7 to 26 d. The experimental design was a 2 x 2 factorial design testing 2 wheat cultivars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
40
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 25 publications
8
40
2
Order By: Relevance
“…Differences in resource allocation to digestive organs, observed between the broilers bred for high body weight (Katanbaf et al 1988;Mitchell and Smith 1991) and for high digestive efficiency specifically (Péron et al 2006), suggest selecting for digestive efficiency may actually compromise other traits which are incorporated into modern breeding programs and vice versa (Pym et al 2004). Contrasting correlations in relative organ sizes have been discovered between lines selected for commercial objectives and high digestive efficiency (Carré et al 2005;Péron et al 2006;Rougière and Carré 2010;de Verdal et al 2010).…”
Section: Feed Intake Digestion and Absorptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Differences in resource allocation to digestive organs, observed between the broilers bred for high body weight (Katanbaf et al 1988;Mitchell and Smith 1991) and for high digestive efficiency specifically (Péron et al 2006), suggest selecting for digestive efficiency may actually compromise other traits which are incorporated into modern breeding programs and vice versa (Pym et al 2004). Contrasting correlations in relative organ sizes have been discovered between lines selected for commercial objectives and high digestive efficiency (Carré et al 2005;Péron et al 2006;Rougière and Carré 2010;de Verdal et al 2010).…”
Section: Feed Intake Digestion and Absorptionmentioning
confidence: 99%
“…Contrasting correlations in relative organ sizes have been discovered between lines selected for commercial objectives and high digestive efficiency (Carré et al 2005;Péron et al 2006;Rougière and Carré 2010;de Verdal et al 2010). For instance, Mussini (2012) showed that the gizzard is significantly smaller, and the pancreas similar, in modern commercial breeds when compared to old-type breeds fed on the same diet.…”
Section: Feed Intake Digestion and Absorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Correlations between this and other performance traits, such as body weight (BW) gain and FCR were either low or negligible; suggesting that selection for P bioavailability will not affect adversely the performance (Zhang et al, 2003). The attempts of Carré et al (2008;Mignon-Grasteau et al, 2004;Pé ron et al, 2006) to select for overall digestive efficiency in broiler chickens have been more promising, as they reported relatively high heritabilities (0.33 to 0.47) for energy, lipid, starch and protein digestion efficiencies for 3-week-old broilers fed on a wheat-based diet in birds selected for digestive efficiency (Mignon-Grasteau et al, 2004). Interestingly, these differences had disappeared by 8 weeks of age and were affected greatly by diet type (Pé ron et al, 2006;Carré et al, 2008).…”
Section: Poultrymentioning
confidence: 99%